Pengaruh Perilaku Konsumen dan Kualitas Pelayanan terhadap Minat Beli pada PT. Mulia Cipta Abadi Medan - Rocky Louis Linardi; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin Syawaluddin (Universitas Batanghari Jambi, 2022)
Consumer behaviour is dynamic, it involves the interaction between affect and cognition, behaviour and events arount it, and involves exchange. Service quality is the totally of features and characteristics of a product or service that depend on its ability to satisfy stated or implied needs. Purchase interest one of the indicators used by company to measure the success or failure of a product / service that is marketed in the community. The research sample used the saturated sample method, so that the entire population was used as the research sample. This research used Likert scale. The results showed that partially each consumer behavior and service quality had a significant positive effect on buying interest. Simultaneously variable of consumer behavior and service quality has a significant positive effect on buying interest.